The Effect of Capital Structure and Profitability on the Value of Pharmaceutical Companies Listed on the Indonesia Stock Exchange - Fenty Fauziah; Tri Munawwaroh; Nita Rislawati (MEC-J (Management and Economics Journal), 2023)
Study this aim for analyze and explain influence capital structure and profitability to score company on company industry pharmacy on the Indonesia Stock Exchange. Population study this is company pharmacy listed on the Indonesia Stock Exchange period observation year 2019-2021. Methodology study this use purposive sampling method with total 8 companies. Analysis on research this conducted with use analysis multiple linear regression and assumption test classic on the SPSS program. by Partial results analysis panel data regression shows that influential capital structure positive significant to score company. Influence profitability by Partial show that results analysis influential panel data regression positive significant to score company. DER and ROA variables individually simultaneous show that take effect positive significant to score company. Enhancement price good stock take effect to decision investment. The more many investors invest, then will raise score company. Good profitability for company that is show ability company produce profit clean. High profitability will influence price stock later will attract investors to buy stock.